Desempenho, características de carcaça e a utilização da carne de ovelhas de descarte terminadas em pastagem cultivada na elaboração de embutido fermentado - François, Poliana (2009)
Aiming to test the inclusion of sheep meat in different proportions which swine meat on the quality of fermented sausage 18 culling sheep crossing Ile de France and Texel race were maintained in pearl millet (Pennisetum americanum L. Leeke) during 75 days. Was followed the performance and evaluated the carcass trait of sheep. The animals were weighed at the beginning of grazing (IP) and before slaughter (PA), and intermediate weighing, every 15 days, to calculate the average daily weight gain (GMD). The carcasses were chilled for 24 hours and then assessed the carcass yield, conformation and fat cover. In the left half were evaluated the carcass length, leg length, arm length, chest depth, fat thickness and marbling, texture and color of meat. It was used to produce sausage meat of the leg, shoulder and neck s sheep and ham and fat swine. The sausage was prepared with 0%, 15%, 35%, 55% and 75% of sheep meat in the formulation, and in all treatments it was used 10% of swine fat. The evolution of pH and water activity (aw) during maturation was evaluated. It was determined, still, the pH, aw, weight loss, microbiological quality, fatty acids profile and sensory analysis of sausage. There was an analysis of the Pearson correlation between the main measures of carcass. The animals showed, on average, an GMD of 140 grams. The yield of commercial cuts of shoulder and leg, showed no correlation with body weight or with the carcass yield, and was 17.9 and 32% respectively. The length of carcass was the feature that showed higher correlation with the hot carcass weight (r = 0621) and cold (r = 0606). The inclusion of sheep meat in the formulation changes the pH, aw and weight loss. The treatments with sheep meat in formulation had lower pH than the sausage without sheep in the formulation. In sensory analysis, the sausage prepared with 15% of sheep meat in the formulation was considered higher than the sausage formulated just with swine meat considering color, flavor and texture features. There is no difference in the smell of sausage when sheep meat was added in the formulation.